University of Minnesota Surgical Clerkship Simulation Skills Curriculum and Instructor Guide - Robert Acton; Connie Schmitz; Jeffrey Chipman; Troy Reihsen; Julie Gilkeson; Shawn Groth; John Raymond; Paula Latz; William Gamble (Association of American Medical Colleges, 2010)
Abstract Introduction The University of Minnesota Medical Student Curriculum for Simulation-Based Training of Procedural Skills was written by faculty and residents who teach third-year surgery clerkship students at the University of Minnesota Simulation Center. The curriculum covers skills expected of entering first-year surgical residents; components may be applicable to other departments and for fourth-year electives as well as clerkships. Methods The curriculum is composed of three sessions that cover fundamental surgical skills, basic bedside procedures, and advanced procedures, followed by an objective structured assessment of technical skills (OSATS). The three sessions require approximately 12 hours of direct instruction and supervised practice, while the OSATS requires approximately 40 minutes. This resource includes detailed session plans (i.e., overview, learning objectives, session agenda, teaching points, assigned readings and hyperlinks), student self-assessment tools, the OSATS instrument and materials related to rater training and grading, and PowerPoint "cook books" that describe the simulation models used in the curriculum. Results In the 2008-2009 academic year, students reported a high level of satisfaction with the course. On a 5-point scale, Session 1 received a mean 4.70 for importance and 4.42 for an overall rating. Session 2 received a mean of 4.64 for importance and 4.38 for an overall rating. Session 3 received 4.51 for importance and 4.15 for an overall rating. To evaluate the curriculum, in the 2007-2008 academic year we administered the 40-minute performance test (OSATS) to 27 students who had received the previous skills curriculum, and to 167 students (2008-2009) who received the new curriculum. We found that mean scores were significantly higher for the new-curriculum group on three of the four performance measures: the checklist item total (83% correct vs. 62%, p = < 0.000), the average global item score (3.62 vs. 3.09, p = 0.003) and the OSATS total score (72% correct vs. 62%, p = < 0.004). There were no differences between the two groups in terms of time to completion. Additionally, we have observed that the overall curriculum, the simulation models, and the instructor guide have ensured consistent coverage of intended content and enhanced the educational experience for students. Discussion Having clear goals and expectations, defined timelines and exercises, reproducible models, equipment lists, student assessment checklists and handouts, and a standardized performance exam gives the simulation center a greater sense of confidence in the product being delivered. Instructor investment and morale have been high, especially in the coaching sessions. The curriculum has been proven a valuable training ground for surgical residents who are interested in a teaching career.